2003
DOI: 10.1152/japplphysiol.00124.2002
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-year change in body composition as measured by DXA in a population-based cohort of older men and women

Abstract: Changing body composition has been suggested as a pathway to explain age-related functional decline. No data are available on the expected changes in body composition as measured by dual-energy X-ray absorptiometry (DXA) in a population-based cohort of older persons. Body composition data at baseline, 1-yr follow-up, and 2-yr follow-up was measured by DXA in 2,040 well-functioning black and white men and women aged 70-79 yr, participants of the Health, Aging, and Body Composition Study. After 2 yr, a small dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 25 publications
12
126
2
3
Order By: Relevance
“…This could have influenced our results, because different studies have shown a decrease of FM in elderly subjects starting after age 70 years. 37,38 In addition, the relationship between fat and lean mass is known to be influenced by ethnicity. 18 As we only investigated Caucasians, our results are not transferable to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…This could have influenced our results, because different studies have shown a decrease of FM in elderly subjects starting after age 70 years. 37,38 In addition, the relationship between fat and lean mass is known to be influenced by ethnicity. 18 As we only investigated Caucasians, our results are not transferable to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…There were 15 African Americans and two Asian Americans in this cohort, with remainder of subjects being Caucasian. This could result in variability in the amount of thigh SM mass change detected, as there is evidence that the amount of SM lost and increases in fatty infiltration in SM varies between Caucasians and African Americans with aging (Visser et al, 2003;Song et al, 2004). Second, this ST protocol only targeted the knee extensors.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect is that with age people become often less active, which contributes to reduced total energy expenditure and has effects on energy balance (Slawik and Vidal-Puig 2006). Usually, AT increases in middle age and declines at the end of life (Visser et al 2003), and during the process of ageing, fat is redistributed from subcutaneous to abdominal depots and to liver, muscle, and other ectopic sites (Kuk et al 2009). These features may per se determine organic failure through lipotoxicity.…”
Section: Ageingmentioning
confidence: 99%
“…Interestingly, the adipocyte number in AT depots in obese individuals declined between 45 and 65 years of age (Virtue and Vidal-Puig 2010;Spalding et al 2008). Metabolic responsiveness decrease at the end of life (Slawik and Vidal-Puig 2006;Visser et al 2003), and there is an age-related decline in expression of pro-adipogenic transcription factors such as PPARγ or C/EBPα (Karagiannides et al 2001). As ATE may fail with advancing age, the need for increased storage of fat may lead to ectopic fat deposition, i.e., in muscle or bone marrow (Slawik and Vidal-Puig 2006;Rudman et al 1991).…”
Section: Adipose Tissue Expansionmentioning
confidence: 99%